Demographic Differences in Disruptive Mood Dysregulation Disorder Symptoms in ADHD, Autism, and General Population Samples. Issue 8 (June 2019) - Mayes, Susan D.; Calhoun, Susan L.; Waxmonsky, James G.; Kokotovich, Cari; Baweja, Raman; Lockridge, Robin; Bixler, Edward O.
Objective: Diagnostic and Statistical Manual of Mental Disorders (5th ed.; DSM-5 ) disruptive mood dysregulation disorder (DMDD) is a controversial new diagnosis. No studies have investigated DMDD symptoms (irritable-angry mood and temper outbursts) and demographics in general population and psychiatric samples.Method: Maternal ratings of DMDD symptoms and diagnoses, age, gender, IQ, race, and parent occupation were analyzed in general population ( n = 665, 6-12 years) and psychiatric samples ( n = 2, 256, 2-16 years).Results: Percentage of school-age children with DMDD symptoms were 9% general population, 12% ADHD-I, 39% ADHD-C, and 43% autism. Male, nonprofessional parent, and autism with IQ > 80 were associated with increasing DMDD symptoms, but demographics together explained only 2% to 3% of the DMDD score variance.Conclusion: Demographics contributed little to the presence of DMDD symptoms in all groups, whereas oppositional defiant disorder (ODD) explained most of the variance. Almost all children with DMDD symptoms had ODD suggesting that DMDD may not be distinct from ODD.